Keberhasilan Event Organizer dalam Meningkatkan Brand Awareness dan Brand Loyalty: Studi Strategi Komunikasi Pemasaran Word Of Mouth dan Public Relations pada Redline Production Surabaya - Louise Emmanuel; Nurhadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the success of event organizers in increasing brand awareness and brand loyalty as well as the reasons why Redline Production uses word of mouth and public marketing communication strategies. This research was conducted using data collection techniques through in-depth interviews and observations to identify WOM and PR marketing strategies in increasing brand awareness and brand loyalty. The results of this research are due to the small environment so that it can build and maintain closer relationships with potential clients and clients. Implementation of WOM elements consists of talkers, lead agents who have strong influence and trust from clients so that they can bring up topics related to service quality and the collaboration process that will be carried out. The tool used is the use of coupons with the company logo to stimulate conversation. Participate by responding to feedback from clients including taking a part, tracing, namely by utilizing agents and vendors as quality control. Implementation of PR elements consists of pull, by providing the best service so as to create a satisfying experience. At push by preparing the event layout and conducting location surveys, then, at pass providing service and education to clients.